Poland vs Spain in the First Decade After EU Accession. Parallel Convergence Patterns? - Piotr Wojcik (Institute of Economic Research (IER), 2017)
Poland and Spain share many common features resulting both from similarities of historical experience and also cultural, political, socio-demographic factors. Both countries have similar area, population and GDP structure. They also share historical experience related to political and economic transformation after a long period of non-democratic, centralized governments. Therefore the experience of Spanish membership in the EU is often considered as a model for Poland. The purpose of this research is to perform a comparative empirical analysis of income convergence processes in Poland and Spain on a regional level (NUTS3). We aim to verify if and how these processes are related to one another (show similar paths). Special attention is paid to the periods after accession of these countries to the EU. Convergence patterns in both countries are compared with several tools. Spatial econometric model for absolute beta convergence, sigma convergence indicators and the analysis of distribution dynamics - transition matrices. The impact on EU accession on income convergence in Spain was positive both on a national and regional level. Regional convergence processes sped-up and interregional disparities decreased. The poorest subregions had relatively high probability to increase their income and catch-up with initially more developed regions. In the first decade after accession to EU Poland has also achieved a significant improvement of income indicators on a national level. However, empirical analyses of GDP per capita distribution and its dynamics on a regional level in Poland show that the above mentioned progress does not spread out proportionally on all regions. Neither beta nor sigma convergence is observed. Instead, relatively fastest growth of initially richest regions (mostly large cities) introduces convergence of clubs leading to polarization. EU accession accelerated divergence processes in Poland.
Keywords: O15; P25; R11; C21; 330; Poland vs Spain; parallel regional convergence; convergence of clubs; distribution dynamics; spatial model